Estimating Fault Location Based on Fault Current in 20 kV Distribution System - Ricky Maulana; Syarif Hidayat (Department of Electrical Engineering ITS and FORTEI, 2020)
The growth of the electric power system is currently taking place rapidly, causing an increase in the number and length of line to provide consumer services. In the line, there are often fault caused by lightning, storms, breakdown insulation, and short circuit caused by birds and other objects. Detection and location determination will speed up the repair process and can avoid more severe damage. Most studies refer to the fault location on the transmission line. But lately the determination of fault location in distribution system has begun to become a concern of researchers for the improvement of the quality of electricity services to consumers. This study discusses the determination of fault locations based on fault currents and the types of disturbances using data from the assumed distribution system model. The estimated fault location by ignoring the fault resistance has the largest error obtained 0.74% and estimated fault location by including fault resistance will cause a very large error, but the error can be reduced by changing the algorithm of the fault resistance assumption. The result for to ground fault error has reached 1.238% and double line to ground error has reached 88.167%.Keywords: distribution system, fault current, fault location, fault resistance.